2003
DOI: 10.1021/jm0205752
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of Sub-micromolar Inhibitors by the Epinephrine-Synthesizing Enzyme Phenylethanolamine N-Methyltransferase

Abstract: The crystal structures of human phenylethanolamine N-methyltransferase in complex with S-adenosyl-l-homocysteine (7, AdoHcy) and either 7-iodo-1,2,3,4-tetrahydroisoquinoline (2) or 8,9-dichloro-2,3,4,5-tetrahydro-1H-2-benzazepine (3, LY134046) were determined and compared with the structure of the enzyme complex with 7 and 7-aminosulfonyl-1,2,3,4-tetrahydroisoquinoline (1, SK&F 29661). The enzyme is able to accommodate a variety of chemically disparate functional groups on the aromatic ring of the inhibitors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 33 publications
8
37
0
Order By: Relevance
“…15 The docking of inhibitors into the hPNMT active site was performed on the R-enantiomer as a previous study on 3-hydroxymethyl-7-substituted-THIQs indicated that the R-enantiomer is preferred over the S-in the hPNMT active site. 32 Residues Lys57 and Met258 move within the PNMT active site depending on the hydrophobicity of the 7-substitutent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The docking of inhibitors into the hPNMT active site was performed on the R-enantiomer as a previous study on 3-hydroxymethyl-7-substituted-THIQs indicated that the R-enantiomer is preferred over the S-in the hPNMT active site. 32 Residues Lys57 and Met258 move within the PNMT active site depending on the hydrophobicity of the 7-substitutent.…”
Section: Resultsmentioning
confidence: 99%
“…32 Residues Lys57 and Met258 move within the PNMT active site depending on the hydrophobicity of the 7-substitutent. 15 Inhibitors that contain a 7-nitro substituent were docked into the crystal structure of hPNMT co-crystallized with SK&F 29661 (4), 16 whereas inhibitors that possess a 7-bromo substituent were docked into the crystal structure of hPNMT cocrystallized with 7-iodo-THIQ (3). 15 The amino acid residues surrounding the 3-position of the co-crystallized ligands SK&F 29661 (4) and 7-iodo-THIQ (3) remain in similar positions in both crystal structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between the amine group of THIQ inhibitors and Glu219 are known to play a key role in their binding to hPNMT. [20][21][22] The amine group of 11 is predicted to interact with Glu219 in the same manner as that of 6. According to the docking studies with 11, it is apparent that, in order for 8-substituted-THBQs to bind in the active site of hPNMT, a significant shift of Val53 away from the 8-substituent or a shift of the inhibitor in the active site would be required.…”
Section: Hpnmt Docking Studies With 8-substituted-thbqsmentioning
confidence: 99%
“…26 To help explain the reduced hPNMT inhibitory potency of the 3-trifluoromethyl-THIQs, molecular docking calculations were conducted using AutoDock 3.0 27 and Sybyl 6.9. 28 Compound 5b was docked into the hPNMT active site based on the X-ray crystal structure of hPNMT-2-AdoHcy (Fig.…”
mentioning
confidence: 99%